Effectiveness of Acupuncture in the Treatment of Hyperemesis Gravidarum: A Systematic Review and Meta-Analysis. (28th July 2021) - Lu, Haizhen; Zheng, Chengwen; Zhong, Yanmei; Cheng, Linhao; Zhou, Yi
Abstract : Background . Hyperemesis gravidarum (HG) is a common gastrointestinal disease afflicting gravidas. It usually results in hospital admission in early pregnancy. Objective . Through a meta-analysis, this study intended to explore acupuncture's clinical efficacy in treating HG. Materials and Methods . A comprehensive search of PubMed, the Cochrane Library, EMBASE, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Biological Medical (CBM), Wanfang Database, and China Science and Technology Journal (VIP) for published clinical randomized controlled trials (RCTs) of acupuncture for treating HG was conducted from the date of database creation to 20th January 2021. We also searched grey literature in four databases: Chinese Cochrane Center, Chinese Clinical Trial Registry, GreyNet International, and Open Grey from their inception to 20th January 2021. Two authors independently screened the literature, extracted data, and evaluated the quality of the literature with Cochrane Handbook 5.1.0 and Review Manager 5.2 software. Review Manager 5.2 and STATA 12.0 software were applied to analyze data. Heterogeneity analysis was performed by the Cochran Chi-square test and I 2 statistic. Egger's tests together with funnel plots were used to identify publication bias. Results . A total of 16 trials covering 1043 gravidas were included. Compared with the conventional treatment, acupuncture had a significantly higher effective rate (OR: 8.11, 95% CI: 5.29∼12.43; P < 0.00001 ), a higher conversion rate of urine ketone (RR: 1.36, 95% CI: 1.15∼1.60; P = 0.0003 ), an improvement rate of nausea and vomiting (OR: 26.44, 95% CI: 3.54∼197.31; P = 0.001 ), and a relatively higher improvement rate of food intake (RR: 1.17, 95% CI: 1.01∼1.36; P = 0.04 ). Acupuncture also shortened hospitalization time and manifested with a lower pregnancy termination rate and fewer adverse events. Nevertheless, no statistical variation in the improvement of nausea intensity, vomiting episodes, and lassitude symptom, recurrence rate, and serum potassium was observed. Conclusion . Our study suggested that acupuncture was effective in treating HG. However, as the potential inferior quality and underlying publication bias were found in the included studies, there is a need for more superior-quality RCTs to examine their effectiveness and safety. PROSPERO registration number: CRD42021232187.